JUNB O‐GlcNAcylation‐Mediated Promoter Accessibility of Metabolic Genes Modulates Distinct Epithelial Lineage in Pulmonary Fibrosis - Marie‐Therese Bammert; Meshal Ansari; Leoni Haag; Zuhdi Ahmad; Victoria Schröder; Joseph Birch; Diana Santacruz; Werner Rust; Coralie Viollet; Benjamin Strobel; Alec Dick; Florian Gantner; et al. (Advanced Science)
Abstract Idiopathic pulmonary fibrosis (IPF) is a lethal disease with substantial unmet medical needs. While aberrant epithelial remodeling is a key factor in IPF progression, the molecular mechanisms behind this process remain elusive. Harnessing a 3D patient‐derived organoid model and multi‐omics approach, the first inventory of the connection between metabolic alteration, chromatin accessibility, and transcriptional regulation in IPF aberrant epithelial remodeling is provided. This remodeling is characterized by an increase in chromatin accessibility, particularly at JUNB motif‐enriched promoter regions proximal to transcription start sites of metabolic and pro‐fibrotic genes. Mechanistically, JUNB undergoes O‐linked β‐N‐acetylglucosamine modification (O‐GlcNAcylation), a critical step in modulating pro‐fibrotic responses to chronic injury. This modification is pivotal in fostering the emergence of aberrant epithelial basal cells in the alveolar niche, a proposed driver of IPF pathology. Specific deletion of O‐GlcNAcylation sites on JUNB attenuates the metaplastic differentiation of basal cells, thereby aiding in the restoration of the alveolar lineage. Together, the findings reveal a novel link between metabolic dysregulation and cell fate regulation at the chromatin level in fibrosis, mediated by the O‐GlcNAc‐JUNB axis, suggesting avenues for the development of new therapeutic strategies in IPF.